Employability: significant signs of the present - Fejes, Andreas; Berglund, Gun (Arbetsmarknad & Arbetsliv, 2018)
Employability has gained renewed attention in contemporary political discussions during the last ten years. The concept has emerged as a signifier which has replaced the previous way of describing the workforce, thereby producing different kinds of pictures of whom is a desirable worker. This article aims to gain a broader understanding of how discourses on employability position care workers in elderly care as responsible for their own employability. Drawing on the Foucauldian concept of governmentality, transnational policy texts and interview transcripts from interviews with care workers are analysed and compared. The main questions are: How are care workers in elderly care made responsible for their own employability and how does this relate to the responsibility assigned to entities such as employers and the state?